The Arabidopsis MYB96 Transcription Factor Mediates ABA-Dependent Triacylglycerol Accumulation in Vegetative Tissues under Drought Stress Conditions - Lee, Hong Gil (Plants (Basel), 2019)
Triacylglycerols (TAGs), a major lipid form of energy storage, are involved in a variety of plant developmental processes. While carbon reserves mainly accumulate in seeds, significant amounts of TAG have also been observed in vegetative tissues. Notably, the accumulation of leaf TAGs is influenced by environmental stresses such as drought stress, although underlying molecular networks remain to be fully elucidated. In this study, we demonstrate that the R2R3-type MYB96 transcription factor promotes TAG biosynthesis in Arabidopsis thaliana seedlings. Core TAG biosynthetic genes were up-regulated in myb96-ox seedlings, but down-regulated in myb96-deficient seedlings. In particular, ABA stimulates TAG accumulation in the vegetative tissues, and MYB96 plays a fundamental role in this process. Considering that TAG accumulation contributes to plant tolerance to drought stress, MYB96-dependent TAG biosynthesis not only triggers plant adaptive responses but also optimizes energy metabolism to ensure plant fitness under unfavorable environmental conditions.